ALTERNATIVE MODEL FOR EVALUATING AERODROME CAPACITY BASED ON PRIORITIZED QUEUE SERVICE - A. K. Mitrofanov; M. A. Petrov; L. E. Rudel’son (Научный вестник МГТУ ГА)
Model of priority service of aerodrome operations is analyzed. The assumption of the legality of replacing the random variable queue length at its most probable value is used. The model is characterized in that the take-off and landing are described not by means of only safety priorities, but by technical and flight characteristics as well. Evaluations of the service waiting time of service and the probability of failure (or re-service) were obtained.ICAO experts have put forward the concept of "System Wide Information Management" and "Collaborative Air Traffic Management", which require for their introduction of new instruments operational management decision making for air traffic services. It should provide participants with the joint organization of new software for rapid analysis of computer results. One of the possible directions of such support is discussed in this article.Analysis of the two priority model shows that the efficiency of priority service is reduced in the case of a large spread of values of average request processing time. As a result of the loss probability for both types of requests become comparable or even approximately equal.Experiment with the five priority flows confirms the order of request losses in accordance with an increase of flow index, identified by formulas for an arbitrary number of input streams. The tendency of the values for the partial converging efficiency criterion of service can only be observed in non-real case where the values of the average service time varies several hundred times. Moreover, this effect can easily be compensated by a slight increase in volume of storage buffer. It becomes obvious that the best conditions for the maintenance of the flow of requests are provided in the case of approximate equality of the average processing times; that is, when all the coefficients of the sequence tend to a single value.The obtained formulas have a sufficient degree of generality and can be used to analyze the priority system in a wide range of data acquisition and processing tasks.